Asymmetric dihydroxylation route to (R)-(-)-octopamine, (R)-(-)-tembamide and (R)-(-)-aegeline - Sadyandy, R.; Fernandes, R. A.; Kumar, P. (Arkivoc, 2005)
A simple and efficient asymmetric synthesis of (R)-(-)-octopamine 1, (R)-(-)-tembamide 2 and (R)-(-)-aegeline 3 is described for the first time employing the Sharpless asymmetric dihydroxylation (AD) as the source of chirality. (C) 2004 Elsevier Science Ltd. All rights reserved.
Keywords: aegeline; Asymmetric synthesis; Dihydroxylation; octopamine; tembamide

Enantioselective synthesis of (+)-(S,S)-reboxetine - Siddiqui, Shafi A.; Narkhede, Umesh C.; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Synlett, 2006)
An efficient enantioselective synthesis leading directly to (+)-(S,S)-reboxetine has been described from commercially available trans-cinnammyl bromide using Sharpless asymmetric dihydroxylation as the key step.
Keywords: coupling; Dihydroxylation; Hydrogenation; reboxetine; trans-cinnamyl bromide

Ring closing metathesis approach to the indole alkaloid mitralactonine - Chavan, Subhash P.; Sharma, Pallavi; Sivappa, R.; Kalkote, Uttam R. (Tetrahedron Letters, 2006)
An efficient utilisation of RCM leading to a convenient synthesis of a pentacyclic indole alkaloid is described. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: corynanthe type alkaloid; Dihydroxylation; mitralactonine; RCM; Swern oxidation

Efficient total synthesis of (-)-(3S,6R)-3,6-dihydroxy-10-methylundecanoic acid - Pandey, Satyendra Kumar; Kumar, Pradeep (European Journal of Organic Chemistry, 2007)
An efficient enantioselective synthesis of (-)-(3S,6R)-3,6-dihydroxy-10-methylundecanoic acid (1) from epichlorohydrin is described. The key steps include Jacobsen's HKR, Sharpless asymmetric dihydroxylation, regioselective opening of epoxide and cyclic sulfate. ((c) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007).
Keywords: cyclic sulfate; Dihydroxylation; Grignard reaction; hydroboration-oxidation; Jacobsen's hydrolytic kinetic resolution (HKR); regio selectivity

First asymmetric total synthesis of penarolide sulfate A(1) - Mohapatra, Debendra K.; Bhattasali, Debabrata; Gujar, Mukund K.; Khan, Mohammad Islam; Shashidhara, K. S. (European Journal of Organic Chemistry, 2008)
Penarolide sulfate A(1), with three contiguous stereogenic centers on a macrocyclic skeleton, affords promise as an alpha-glucosidase inhibitor. Herein, we describe the first asymmetric total synthesis of this natural product. A stereoselective strategy for rapid assembly of the complete framework of the 30-membered macrocyclic core is delineated herein. Sequential amidation and intramolecular Sonogashira cross-coupling reactions were pivotal to the success of our efforts. ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Keywords: Asymmetric synthesis; C-C coupling; Dihydroxylation; epoxidation; Macrocycles; Regioselectivity; Total synthesis

Highly diastereoselective total synthesis of (+/-)-heritonin and (+/-)-heritol - Chavan, Subhash P.; Garai, Sumanta; Kalkote, Uttam R. (Tetrahedron, 2012)
A highly diastereoselective synthesis of heritol and heritonin by intramolecular cyclization on a preformed sensitive butenolide functionality is described. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Butenolide; cyclization; Dihydroxylation; Friedel-Crafts acylation; Tetralone

Synthesis and antimicrobial activity of novel oxysterols from lanosterol - Shingate, Bapurao B.; Hazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V. (Tetrahedron, 2013)
Chemically diverse oxysterols and their synthetic manipulations were carried out from variety of Delta(8(9)_) lanosterol derivatives and evaluated for their in vitro antimicrobial activities. Most of the synthesized oxysterols exhibited significant antifungal activity against the tested strains. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Allylic oxidation; antibacterial activity; Antifungal activity; Dihydroxylation; Oxygenated steroids

Formal enantioselective synthesis of (-)-epiquinamide by proline-catalyzed one-pot sequential -amination/propargylation of aldehyde and asymmetric dihydroxylation of olefin - Ahuja, Brij Bhushan; Emmanuvel, Lourdusamy; Sudalai, Arumugam (Synlett, 2016)
Two independent routes to the formal synthesis of (-)-epiquinamide, have been described: the first route utilizes an l-proline-catalyzed one-pot sequential -amination/propargylation of aldehyde, while the second one employs asymmetric dihydroxylation as the key reaction to install the stereochemistry. While the first synthesis was accomplished in nine steps with 24.4% overall yield and dr 9:1, the second strategy resulted in the synthesis in eight steps with 36.4% overall yield and with perfect enantiocontrol.
Keywords: Amination; diastereoselective; Dihydroxylation; Proline; quinolizidine